Zapatista Education as an Alternative to the Neoliberal Model - Landeros Belmont, Roberto Luciano (2022)
This essay aims to reflect on the negative effects that neoliberalism and the search for modernity have left on Latin American education, as well as the influence of social movements which, to combat the predatory effects of capitalism, have constituted a critical pedagogy linked to an education of the people, with special attention to Zapatista education, which in its struggle for a just, democratic, and free society by designing an educational system derived from critical pedagogy as an alternative to the dominance of a neoliberal education.